2012
DOI: 10.1111/j.1469-8137.2012.04227.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the rice SPX‐MFS family reveals a key role of OsSPX‐MFS1 in controlling phosphate homeostasis in leaves

Abstract: Summary Proteins possessing the SPX domain are found in several proteins involved in inorganic phosphate (Pi) transport and signalling in yeast and plants. Although the functions of several SPX‐domain protein subfamilies have recently been uncovered, the role of the SPX‐MFS subfamily is still unclear. Using quantitative RT‐PCR analysis, we studied the regulation of SPX‐MFS gene expression by the central regulator, OsPHR2 and Pi starvation. The function of OsSPX‐MFS1 in Pi homeostasis was analysed using an OsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 48 publications
(117 reference statements)
4
111
2
1
Order By: Relevance
“…This transcript was one of the most highly induced genes in the roots with more than 1400-fold induction, as well as showing a 30-fold increase in the shoot. This locus also overlapped with the genomic location of O. sativa (osa)-miR827a, one of the key miRNAs involved in Pi homeostasis, which acts through the regulation of two target genes, SPX-MFS1 and SPX-MFS2 (Lin et al, 2010;Wang et al, 2012). This locus was considered to be the precursor of osa-miR827, but no cDNA or ESTs were reported for this locus so far (Lacombe et al, 2008), probably due to the fact that this gene is only expressed under Pi-deficient conditions.…”
Section: Identification Of Mis-and Unannotated Loci Involved In Pi Homentioning
confidence: 99%
See 2 more Smart Citations
“…This transcript was one of the most highly induced genes in the roots with more than 1400-fold induction, as well as showing a 30-fold increase in the shoot. This locus also overlapped with the genomic location of O. sativa (osa)-miR827a, one of the key miRNAs involved in Pi homeostasis, which acts through the regulation of two target genes, SPX-MFS1 and SPX-MFS2 (Lin et al, 2010;Wang et al, 2012). This locus was considered to be the precursor of osa-miR827, but no cDNA or ESTs were reported for this locus so far (Lacombe et al, 2008), probably due to the fact that this gene is only expressed under Pi-deficient conditions.…”
Section: Identification Of Mis-and Unannotated Loci Involved In Pi Homentioning
confidence: 99%
“…Differential expression analysis revealed that osa-miR827 and osamiR399 were the most induced families in both root and shoot, with miR827 being the most induced miRNA after 21 d of Pi starvation, with more than a 140-fold increase seen in roots (Figures 9A and 9B; see Supplemental Data Set 8 online). These two miRNA families have been shown to be induced by Pi starvation in both Arabidopsis and rice Bari et al, 2006;Lin et al, 2010;Jeong et al, 2011;Wang et al, 2012), with Arabidopsis miR399 negatively regulating genes such as PHO2 and the two Pi transporters Pht1;8 Differentially expressed miRNAs in response to 21 d of Pi starvation in the roots (A) and shoots (B) were identified using the miRanalyzer software. Only significantly differentially expressed miRNAs with a fold change greater than 2 are shown (q value < 0.05).…”
Section: Genome-wide Analysis Of the Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The subfamily SPX-MFS (Major Facilitator Superfamily) includes transporters that facilitate the translocation of small solutes, including phosphate [23][24][25]. In A. thaliana there are three members (SPX-MSF1-3).…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
“…When the studies conducted on hopelessness in educational organizations are analyzed, it can be understood that these studies were done especially on teenagers having education (Alverson, 2014;Hoy and Tarter, 2004;Kula, 2008;Siyahhan, Aricak and Acar, 2012), university students (Asdigian, 1993;Kılıç, Tektaş and Pala, 2014;Stockum, 1999;Lamis, Saito, Osman, Klibert, Malone and Langhinrichsen-Rohling, 2014;Üngüren, 2007), preservice teachers (Ceyhan, 2004;Dinçer, Yılmaz and Keşan, 2015;Öngen, 2012;Şahin, 2009;Şengül, Güner and Altın, 2014) and teachers (Kiziroğlu, 2012;Taner, 2008;Yıldırım, 2015). Of the studies conducted in the field of education, for example, the results of the study by Üngüren (2007) on 496 tourism students having education at high schools and universities put forth a positive significant relationship between hopelessness and anxiety and it was concluded that as the anxiety levels of the students increase, their hopelessness levels increase, too.…”
Section: Introductionmentioning
confidence: 99%